Analysis of Result Variability from High-Density Oligonucleotide Arrays Comparing Same-Species and Cross-Species Hybridizations - J.D. Chismar; T. Mondala; H.S. Fox; E. Roberts; D. Langford; E. Masliah; D.R. Salomon; S.R. Head (BioTechniques)
There exists a significant limitation in the variety of organisms for which microarrays have been developed because of a lack of genomic sequence data. A near-term solution to this limitation is to use microarrays designed for one species to analyze RNA samples from closely related species. The assumption is that conservation of gene sequences between species will be sufficient to generate a reasonable amount of goodquality data. While there have been relatively few published reports describing the use of microarrays for cross-species hybridizations, this technique is potentially a powerful tool for understanding genomics in model organisms such as nonhuman primates. Here we describe the analysis and comparison of hybridization characteristics and data variability from a set of crossspecies (rhesus macaque) and same-species (human) hybridization experiments using human high-density Affymetrix oligonucleotide arrays. The data reveal that a large fraction of probe sets are effective at transcript detection in the cross-species hybridization, validating the application of cross-species hybridizations for nonhuman primate genomics research.